Impact of the COVID-19 Pandemic on Myocardial Revascularization in Patients with Acute Coronary Syndrome in the Russian Federation - B. G. Alekyan; S. A. Boytsov; V. I. Ganyukov; E. M. Manoshkina (Рациональная фармакотерапия в кардиологии)
Aim. To compare and analyze the results of myocardial revascularization in the Russian Federation (RF) with acute coronary syndrome (ACS) before the onset (2018-2019) and during the novel coronavirus infection (COVID-19) pandemic (2020-2021).Material and methods. The analysis included the number of cases of ST-segment elevation myocardial infarction (STEMI), non-ST-segment elevation acute coronary syndrome (NSTE-ACS), the number of cases of myocardial revascularization in the above forms of ACS, the number of deaths depending on the form of ACS and the method performed revascularization. The period of time before the start of the coronavirus pandemic corresponded to the annual data received in the Russian Federation for 2018-2019. The period of the coronavirus disease pandemic corresponded to the annual data received in the country for 2020-2021. Absolute, relative, estimated values of patient hospitalization, myocardial revascularization procedures, and mortality in ACS were compared between time periods before and during the COVID-19 pandemic. The data for analysis were obtained from the monitoring of the Ministry of Health of Russia.Results. In 2018 and 2019 in the RF, 531,019 and 501,238 patients were hospitalized with a diagnosis of ACS, and during the pandemic (2020-2021) - 403,931 and 397,930 patients, respectively. Reduction in the number of patients diagnosed with ACS admitted to hospitals in Russia by 22.32% in 2020-2021 years was mainly due to a significant decrease in hospitalizations of patients with a diagnosis of NSTE-ACS (by 29.03%). At the same time, admission to clinics of patients with STEMI decreased only by 6.02%. During the COVID-19 pandemic, mortality increased significantly in PPCI (by 9.6%) and in the general STEMI group (by 12.3%); significantly increased mortality both in the general group (by 48%) and during PCI in patients with NSTE-ACS (by 28.6%); there was an increase in the average annual number of PPCI (by 12.6%), which was accompanied by an increased average annual number of PPCI per 1 million of population (up to 451 per 1 million of population); a slight increase in the average time "symptom-balloon" (by 2 minutes) was recorded; there was an absolute slight decrease and a relative increase in the number of PCIs in NSTE-ACS (by 2.7% and 37.1%, respectively). In 2021, in the Russian Federation, primary PCI was performed in 50.2%, thrombolytic therapy - in 23.1%, and 26.7% of patients remained without reperfusion. Pharmacoinphasive strategy was applied in 60%, and isolated thrombolysis - in 40% of patients.Conclusion. During the COVID-19 pandemic, revascularization in patients with ACS in Russia corresponded to the following trends recorded in the literature: increased hospital mortality in PPCI and in the general STEMI group; hospital mortality both in the general group and during PCI in patients with NSTE-ACS. The indicators of myocardial revascularization in ACS in the RF during the pandemic were fundamentally different from the data of Western countries: there was an increase in the average annual number of PPCI and the average annual number of PPCI per 1 million population; a slight increase in the average symptom-balloon time was recorded; revealed an absolute slight decrease and a relative increase in the number of PCIs in NSTE-ACS.